Analisis Niat Adopsi Aplikasi Bank Digital menggunakan UTAUT dan DeLone & McLean - Irsan, Yusuf Nabiil; Utami, Meinarini Catur; Fetrina, Elvi (Prodi Sistem Informasi Universitas Dharma Andalas, 2025)
Digital banks generally lose money in their first 2-3 years, because most of the company's funds are invested in technology. The number of digital banks in Indonesia is expected to continue to grow every year. The increasing number makes competition between banking companies increasingly fierce in terms of attracting users to achieve high incomes. The large amount of digital banking provides various options for the Indonesians to choose the application services according to personal preferences. The purpose of this study was to determine what factors influence a user in making the intention to adopt a digital banking application. This quantitative research was conducted using the Partial Least Square SEM analysis method using the SmartPLS tool. As many as 400 data samples were used, obtained through purposive sampling techniques spread across Jabodetabek. The results of the study showed that system quality, social influence, and facilitating conditions were the factors that influenced users in their intention to adopt digital banking applications. This shows that digital banking companies need to improve these three aspects in order to acquire new users to gain profits and be able to compete amidst the increasing emergence of digital banking applications in Indonesia.